Dendrimer-based nanoparticles in tissue engineering and regenerative medicine approaches - Oliveira, Joaquim M. (2012)
Dendrimeric macromolecules are synthetic and spherical systems that have been attracting great deal of attention as nanocarriers for intracellular drug delivery (DDS) [1]. These possess several advantages as nanocarriers, as it possibly incorporating smart functionalities such as targetability and stimuli-responsive drug release. Our group has been proposing the use of dexamethasone (Dex)-loaded carboxymethylchitosan/ polyamidoamine dendrimer nanoparticles (CMCht/PAMAM NPs) [2,3] for controlling the differentiation of stem cells towards the osteogenic lineage. In this work, the biocompatibility of the Dex-loaded CMCht/PAMAM NPs were investigated, in vitro and in vivo. CMCht/PAMAM NPs were produced as described by Oliveira et al. [4]. Dexamethasone (Dex) was loaded into the NPs by means of using a precipitation route. Dex-loaded NPs were chemically bound to fluorescein isothiocyanate (FITC) for styding their intracellular fate. The cellular uptake of NPs was investigated using different cell types namely rat bone marrow stromal cells (RBMSCs) and Human Osteosarcoma cell line (SaOS-2), for times up to 14 days of culturing. The internalization of the FITClabelled and Dex-loaded CMCht/PAMAM dendrimer NPs waere investigated using fluorescence microscopy and flow cytometry (FACS) analyses. FITC-labelled NPs (1 lg/g and 10 lg/g) were injected intraveneously on Wistar rats and its biodistribution in different organs was evaluated up to 72 h. Results have revealed that Dex-loaded CMCht/PAMAM dendrimer NPs are non-cytotoxic, in vitro and in vivo. The in vivo studies also revealed that CMCht/PAMAM dendrimer NPs are stable in circulation. The histological study has shown that NP’s are uptaken by cells from different tissues/organs namely, brain, liver, kidney and lung. This study has revealed that the dexamethasone-loaded CMCht/PAMAM dendrimer nanoparticles are non-toxic and demonstrated a great ability for being uptaken by different cell types. Moreover, we have demonstrated that the dexamethasone-loaded CMCht/ PAMAM dendrimer nanoparticles are able to control stem cells osteogenic differentiation. As a final conclusion, the developed nanocarriers are advantageous as intracellular nanocarrier tools for preprogramming the stem cells fate ex vivo. The developed dexamethasone-loaded CMCht/PAMAM dendrimer nanoparticles showed great promise for application in bone tissue engineering strategies as it allowed us to produce de novo bone tissue in vivo.